Adenoid cystic carcinoma of the gastroesophageal junction: A case report. Issue 35 (August 2019) - Shou, Chun-Hui; Li, Zhi-Jian; Yang, Wei-Li; Tjhoi, Welda E.H.; Zhao, Zhi-Cheng; Yu, Ji-Ren
Abstract: Rationale: Adenoid cystic carcinoma (ACC) rarely occurs in the digestive tract, particularly in the gastroesophageal junction. Patient concerns: A 44-year-old male vomiting blood was admitted to our hospital. Endoscopic ultrasound showed a 2.2 × 3.0 cm submucosal tumor in the gastroesophageal junction. Diagnosis: According to the histopathological examination, the tumor was composed predominantly of ductal epithelial and myoepithelial cells. Immunohistochemical staining revealed that the tumor expressed cytokeratin, cluster of differentiation 117, p63, and calponin. Based on these findings, ACC was diagnosed. Interventions: Endoscopic submucosal dissection (ESD) was performed to remove the tumor. As the margins of the ESD specimen were positive, the patient underwent total gastrectomy with D2 lymphadenectomy. Finally, neither residual tumor nor lymphatic metastasis was detected in the surgical specimens. Outcomes: No sign of recurrence has been detected during 36 months of follow-up as of October 2018. Lessons: ESD may be an alternative treatment for cardial ACC invading the submucosa.